Phosphorylation of threonine residues on Shc promotes ligand binding and mediates crosstalk between MAPK and Akt pathways in breast cancer cells. (January 2018) - Suen, K.M.; Lin, C.C.; Seiler, C.; George, R.; Poncet-Montange, G.; Biter, A.B.; Ahmed, Z.; Arold, S.T.; Ladbury, J.E.
Abstract: Scaffold proteins play important roles in regulating signalling network fidelity, the absence of which is often the basis for diseases such as cancer. In the present work, we show that the prototypical scaffold protein Shc is phosphorylated by the extracellular signal-regulated kinase, Erk. In addition, Shc threonine phosphorylation is specifically up-regulated in two selected triple-negative breast cancer (TNBC) cell lines. To explore how Erk-mediated threonine phosphorylation on Shc might play a role in the dysregulation of signalling events, we investigated how Shc affects pathways downstream of EGF receptor. Using an in vitro model and biophysical analysis, we show that Shc threonine phosphorylation is responsible for elevated Akt and Erk signalling, potentially through the recruitment of the 14-3-3 ζ and Pin-1 proteins.